Chirality and Chiroptical Effects in Plasmonic Nanostructures: Fundamentals, Recent Progress, and Outlook. (2nd April 2013) - Valev, Ventsislav K.; Baumberg, Jeremy J.; Sibilia, Concita; Verbiest, Thierry
Abstract Strong chiroptical effects recently reported result from the interaction of light with chiral plasmonic nanostructures. Such nanostructures can be used to enhance the chiroptical response of chiral molecules and could also significantly increase the enantiomeric excess of direct asymmetric synthesis and catalysis. Moreover, in optical metamaterials, chirality leads to negative refractive index and all the promising applications thereof. In this Progress Report, we highlight four different strategies which have been used to achieve giant chiroptical effects in chiral nanostructures. These strategies consecutively highlight the importance of chirality in the nanostructures (for linear and nonlinear chiroptical effects), in the experimental setup and in the light itself. Because, in the future, manipulating chirality will play an important role, we present two examples of chiral switches. Whereas in the first one, switching the chirality of incoming light causes a reversal of the handedness in the nanostructures, in the second one, switching the handedness of the nanostructures causes a reversal in the chirality of outgoing light.